Factores de riesgo en artrosis de rodilla en adultos de 70 a 85 años que acuden al Hospital General Martín Icaza de la ciudad de Babahoyo periodo noviembre 2023 – abril 2024. - Cisneros Palmiro, Pamela Nicole (2024)
Knee osteoarthritis, also called osteoarthritis, is a degenerative condition of the cartilage that covers the bony surfaces of the bones (femur, tibia, patella) that make contact within the knee joint, thus preventing friction from causing pain. The main objective of the present investigation was to determine the risk factors for knee osteoarthritis in adults aged 70 to 85 years who attend the Martín Icaza General Hospital in the city of Babahoyo. The methodology used was field, descriptive and quantitative. The results showed that the age group most affected was female, while the ages of older adults with knee osteoarthritis were between 70 and 75 years of age. The study population was overweight, the most frequently mentioned history of joint trauma was a direct blow, the intensity of pain presented by the population was mostly moderate, while after the application of the Barthel index, only half of the study population showed serious dependency. It was concluded that the main risk factors for knee osteoarthritis were age, gender, genetics, race, occupation, joint trauma, vitamin deficiency, weight, bone mineral density, midline alterations (genu varus, valgus), etc. In turn, these could be classified into modifiable and non-modifiable risk factors.